Adaptive functional traits and soil characters drive the successful naturalization of Solanum viarum; An alien species in subtropical forest - Muhammad Waheed; Fahim Arshad; Abeer Al-Andal (Journal for Nature Conservation, 2026)

Genome sequencing reveals genes under selection for olfactory transduction in highland sheep - Anees Ahmad; Muhammad Ibrahim; Muhammad Yaqoob; Muhammad Fahim; Sher Hayat Khan; Israr Ud Din; Majid Khan; Sohail Ahmad (Molecular Genetics and Genomics, 2026)
Kutta is an indigenous sheep breed found in the mountainous region of Swat, Pakistan. In this study we evaluated the performance of Kutta sheep within their natural habitat and identified genomic regions associated with environmental adaptability using whole genome sequencing. Flocks are mostly managed under a transhumant production system with year-round breeding. Kutta sheep demonstrated higher lambing efficiency under the available resources. Although the body size of rams and ewes was comparable, significant variation was observed among different age groups. Whole genome sequencing identified 15.46 million variants relative to Oar_v1.0 reference genome assembly. Exonic variants accounted for 2.3% of all protein coding gene variants and affected 6347 genes. These genes were primarily enriched in pathways related to G protein-coupled receptor signaling (700 genes) and olfactory transduction (500 genes). Selective sweep analysis detected 1930 genes within the regions of high homozygosity across the genome. Based on homozygosity patterns, biological relevance, and colocalization with known QTLs, 11 candidate genes were identified as putative selective signature. Five of these genes (OR4C6L, OR1086L, OR5AK2L, QR5T2L, OR9Q2) belonged to the olfactory receptor family. These olfactory receptor genes may contribute to high-altitude adaptation in Kutta sheep by enhancing their ability to locate food resources, recognize mates, and detect predators in challenging mountainous environments. Further screening of the OR4C6L sequence across 12 indigenous sheep breeds revealed marked differences between highland and lowland populations. Collectively, these findings provide comprehensive genomic insights into high-altitude adaptation of sheep and highlight the potential role of olfactory perception in survival and environmental fitness.

Exploring the bioactivity of Ageratum conyzoides L: Antioxidant, antimicrobial, and cytotoxic properties of flower extracts - Md. Safkat Zaman Fahim; Shyama Prosad Moulick; Sauda Sultana Mimi; Subarna Sandhani Dey; Md. Omar Sha Rafi; Sadia Afrin Chhanda; Dabashes Adhikery; Muhammad Mahfuz Hasan; Shahin Aziz; Tanvir Muslim (Next Research, 2026)

Ecological drivers and conservation prioritization for Withania somnifera: integrating co-occurrence patterns and niche modeling in human-dominated landscapes - Muhammad Waheed; Fahim Arshad; Abeer Al-Andal (Landscape and Ecological Engineering, 2026)

Ethnobotanical documentation of plant resources used for women’s healthcare in Sahiwal division, Punjab, Pakistan - Kaniz Fatima; Muhammad Iqbal; Fahim Arshad; Mari Sumayli; Yehia Hazzazi; Mukhammadjon Matazimov; Muhammad Waheed (Genetic Resources and Crop Evolution, 2026)

Assessing stand development controls on carbon sequestration and carbon credit value in tropical introduced teak plantation - John Oluwafemi Ayoola; Babatunde Oluseyi Ajiboye; Abraham Olanrewaju Opanike; Fahim Arshad; Shiekh Marifatul Haq; Adetayo Olubunmi Odunola; Aderinola Adeola Deborah; Muhammad Waheed; Ismoilov Ibrokhim; Muydinov Nurillo Tukhtarovich; Tursunqulov Jasur Baxtiyorovich; Mamatov Hurshidbek Mirzakamol o‘g‘li (Environmental Monitoring and Assessment, 2026)

Ecological and human health risks from railway-associated contaminants: a case study of trace metal and PAH pollution along a commuter line in Chittagong, Bangladesh - Mahbub Alam; Md. Samrat Mohay Menul Islam; Muhammad Abu Bakar; Md. Ashraful Islam; Suman Das; Sreebash Chandra Bhattacharjee; Kaiser Mahmood Fahim; Md. Hasan Mahmud Babu (Environmental Geochemistry and Health, 2026)

Integrating Urban Growth, Environmental Stress and Public Sentiment through a Multifunctionality-Inspired Spatiotemporal Trade-Off Framework: Evidence from Peshawar, Pakistan - Muhammad Farooq Hussain; Xiaoliang Meng; Syed Fahim Shah; Xinkan Hu (Sustainable Cities and Society, 2026)

Decarbonizing Pakistan's cement sector: Multi-scope emissions inventory, drivers, and mitigation pathways - Unib Arshad Lodhi; Qurratulain; Muhammad Badar Alam; Muhammad Fahim Khokhar (Journal of Cleaner Production, 2026)

Tuning thermochromic performance of 2D perovskites via Br/Cl doping: Enhanced optical modulation and lowered transition temperature toward building energy efficiency - Huanfeng He; Xin Li; Muhammad Fahim; Sai Liu; Irum Firdous; Tsz Chung Ho; Chi Yan Tso (Chemical Engineering Journal, 2026)

Review of risk analysis and management practices for urban water utilities’ sustainability and resilience - Muhammad Fahim Aslam; Farhad Jazaei; Peyman Babakhani; Brian Waldron; Rouzbeh Nazari (Water Resources Management, 2026)
Urban water utilities (UWU) face escalating challenges from rapid urbanization, climate change, aging infrastructure, and institutional fragmentation. This review synthesizes evidence from 62 peer-reviewed studies to critically examine how risk analysis and management are conceptualized and applied in UWU across diverse geographies and economic settings. Through thematic dimensions on geospatial factors, including climate, terrain, population density, Gross Domestic Product (GDP), and water governance structures, along with institutional data, the study employs descriptive patterns, statistical analysis, and cross-regional comparison to explore the distribution and drivers of water risks in UWU. Email correspondence with corresponding authors was conducted to evaluate the implementation status of proposed recommendations and the translation of research findings into practice. The risks are categorized into two types: natural and anthropogenic. The latter includes operational, health and safety, financial, and socio-political risks. The paper evaluates six major risk analysis methodological categories, which vary in terms of data requirements and suitability for different types of risk. These approaches provide valuable interpretations, but many applications represent one issue, often neglecting cascading effects and dynamic interdependencies between risk domains. The review identifies critical research and practice gaps and emphasizes the need for integrated and adaptive risk governance that bridges academic knowledge and utility practice to enhance the resilience of UWU.

In vivo systemic toxicity assessment of Bacillus safensis NMCC-189: a probiotic strain evaluated via short-term tolerability and 28-day repeated-dose (OECD 407) study in Balb/c mice - Maryam Khan Sherwani; Syeda Rida Zainab; Jehan Zeb Khan; Shakira Ghazanfar; Fahim Hilal; Rimsha Noor; Muhammad Khalid Tipu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Biodiversity under threat: the role of native and alien indicator species in assessing forest disturbance and conservation needs - Muhammad Waheed; Fahim Arshad; Abeer Al-Andal; Asma Jabeen; Alessandra De Marco (Biological Invasions, 2026)

Etiology and integrated management of fruit rot of peach (Prunus persica L.) caused by a mycotoxigenic Aspergillus flavus - Palwasha; Siraj ud Din; Muhammad Fahim (European Journal of Plant Pathology, 2026)

Chemical Profile, Biological Activities, Molecular Docking, and Density Functional Theory (DFT) of Cymbopogon citratus Essential Oil Extracted By Conventional and Superheated Steam Extraction Techniques - Muhammad Adnan Ayub; Fiza Bashir; Khayala Mammadova; Muhammad Talha Anjam; Muhammad Ijaz; Amjad Hussain; Mohamed Fawzy Ramadan; Fahim Arshad; Muhammad Zubair (Journal of Pharmaceutical Innovation, 2026)

Cover Image - Faisal Ahmad Lodhi; Fahim Ullah Khan; Aabid Ullah Khan; Jae‐Seong Lee; Muhammad Abbas; Hanafiah Fazhan; Khor Waiho; Menghong Hu; Youji Wang (Reviews in Aquaculture, 2026)
The cover image is based on the article Multi‐Stressor Responses in Marine Bivalves: Integrating Climate Change, Pollutants, and Microbiome Shifts for Aquaculture Resilience by Faisal Ahmad Lodhi et al., https://doi.org/10.1111/raq.70169 . image

Multi‐Stressor Responses in Marine Bivalves: Integrating Climate Change, Pollutants, and Microbiome Shifts for Aquaculture Resilience - Faisal Ahmad Lodhi; Fahim Ullah Khan; Aabid Ullah Khan; Jae‐Seong Lee; Muhammad Abbas; Hanafiah Fazhan; Khor Waiho; Menghong Hu; Youji Wang (Reviews in Aquaculture, 2026)
Marine bivalves play pivotal ecological and economic roles but are increasingly challenged by multiple environmental stressors. Although there is extensive research on the effects of individual stressors, a comprehensive review is needed to synthesize current evidence and clarify how multiple interacting stressors collectively affect the physiology and resilience of marine bivalves. This review integrates evidence from 2010 to 2025, encompassing 178 peer‐reviewed studies emphasizing the combined and interactive impacts of climate change drivers (warming, hypoxia, salinity, and ocean acidification), pollutants (heavy metals, persistent organic pollutants, endocrine‐disrupting chemicals, antibiotics, nanoparticles, microplastics), and microbiome shifts on future aquaculture resilience. Literature was systematically retrieved from Web of Science, Scopus, PubMed, and Google Scholar in accordance with PRISMA 2020 guidelines. Bibliometric mapping (VOSviewer 1.6.20) revealed a rapid growth in research after 2018, characterized by studies on Mytilus , Crassostrea , and Ruditapes . A systematic evaluation of recent evidence was conducted, combining data from physiological, molecular, and microbial studies, with particular attention to implications for aquaculture. The analysis reveals that stressors rarely act alone. Instead, their cumulative and interactive effects cause oxidative stress, disrupted energy allocation, destabilized host‐microbe relationships, lowered tolerance thresholds, and other eco‐physiological consequences. These results highlight the vulnerability of bivalve populations to rapid coastal urbanization, declining water quality, and sediment contamination. The review concludes that resilience can be enhanced through selective breeding for stress‐tolerant genotypes, integrated monitoring of pollutants and microbial indicators, and multi‐omics approaches to guide adaptive aquaculture management.

Seasonal shifts in algal communities driven by environmental gradients in Kallar Kahar Lake, Pakistan - Mubashrah Munir; Rahmatullah Qureshi; Fahim Arshad; Asma Jabeen; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah; Muhammad Waheed (Limnology, 2026)

Remote sensing-based 2D hydrodynamic modeling and assessment of the 2014 flood in the Jhelum river basin - Rizwan Mansha; Sajjad Haider; Muhammad Azmat; Hamza Farooq Gabriel; Fahim Ullah (Modeling Earth Systems and Environment, 2026)

Data fusion for air pollution monitoring: satellite, ground based and ensemble models for PM 2.5 prediction - Afnan Ullah; Kamran; Musawar Hussain; Hira Saif; Muhammad Fahim Khokhar (International Journal of Remote Sensing, 2026)

Leucocoprinus aurantiopileus (Agaricaceae), a New Species from Pakistan - Fazli Maula; Malka Saba; Muhammad Asif; Afifa Kainat Rani; Wajahat Akram; Fahim Ullah; Saher Batool; Kainat Bakhsh; Ayesha Bibi; Aiman Izhar; Najam Ul Sehar Afshan; Abdul Nasir Khalid (New Zealand Journal of Botany, 2026)
A novel species, Leucocoprinus aurantiopileus , is described from Margalla Hills National Park, Islamabad, Pakistan, using an integrated approach. Phylogenetic analyses based on combined internal transcribed spacer and large subunit sequences confirm its placement within Leucocoprinus . L. aurantiopileus is distinguished by a conical to campanulate, subumbonate to umbonate pileus, dark red center, and light orange margins, along with subcylindrical to oblong basidiospores. We provide detailed descriptions, colored photographs, microscopic structures, and a phylogenetic tree. This discovery highlights the mycological diversity of Margalla Hills and emphasizes the need for further fungal exploration in the region.

Coprinellus gregariodiguttulatus , a New Coprinoid Species from Margalla Hills, Islamabad, Pakistan - Fahim Ullah; Malka Saba; Iram Fatima; Muhammad Asif; Mohsin Ullah; Fazli Maula; Wajahat Akram; Amir Sohail (New Zealand Journal of Botany, 2026)
Coprinellus gregariodiguttulatus is described as a new species from Quaid‐i‐Azam University, Islamabad, Pakistan, based on morphological and molecular analyses. The species is distinguished by its small gray to light gray basidiomata, paraboloid to hemispherical pileus, and oblong to obovoid or rarely lemon basidiospores. Phylogenetic analysis of the internal transcribed spacer (ITS) region supports its placement within Coprinellus sect. Disseminati is a distinct lineage, closely related to but separate from other known taxa. This discovery from an underexplored region highlights the potential for uncovering further novel fungal diversity in Pakistan.

Carbon sequestration and credit potential of native and non-native monoculture plantations in a subtropical irrigated forest - Muhammad Waheed; Shiekh Marifatul Haq; Abeer Al-Andal; Fahim Arshad; Muhammad Iqbal (Biomass and Bioenergy, 2026)

Adaptive morphological and physiological strategies of Sporobolus ioclados in desert ecosystem - Muhammad Akram; Nargis Naz; Ummar Iqbal; Syeda Refat Sultana; Fahim Arshad; Muhammad Waheed; Muhammad Adeel Ghafar; Hafiz Muhammad Mohsin Hassan; Arslan Asghar; Abeer Hashem; Dalal Saad Alharbi; Graciela Dolores Avila-Quezada; et al. (The Science of Nature, 2026)

Determination of the Chemical Profile of Hibiscus rosa-sinensis L. Leaves Using Different Solvents and Evaluation of their Antioxidant, Antimitotic, and Antiproliferative Potentials - Sehrish Sadia; Muhammad Waheed; Tahira Rashid; Murad Muhammad; Huma Bashir; Fahim Arshad; Muhammad Iqbal; Abeer Hashem; Khalid F. Almutairi; Elsayed Fathi Abd-Allah (Journal of Pharmaceutical Innovation, 2026)

Metagenomic Exploration of the Bacteriome Reveals Natural Wolbachia Infections in Yellow Fever Mosquito Aedes aegypti and Asian Tiger Mosquito Aedes albopictus - Gul E. Nayab; Rafi ur Rahman; Fazal Hanan; Inamullah Khan; Muhammad Fahim (Current Microbiology, 2026)

Morphology and phylogeny of gasteroids and two novel hosts for Pisolithus albus (Sclerodermataceae) from Pakistan - Fahim Hussain Shah; Munazza Kiran; Muhammad Binyamin Khan; Abdul Basit; Abdallah M. Elgorban; Mushtaq Ahmad; Tauseef Ullah; Abdul Samad Mumtaz; Sana (New Zealand Journal of Botany, 2025)

From wild ecosystem to the pharmaceutical use–exploring the traditional medicine and socio-cultural heritage of macrofungi from Pakistan - Fahim Hussain Shah; Muhammad Atif Azeem; Tauseef Ullah; Abdul Samad Mumtaz; Sayed Afzal Shah; Muhammad Binyamin Khan; Samantha C. Karunarathna; Abdallah M. Elgorban; Munazza Kiran (New Zealand Journal of Botany, 2025)

Alleviating stocking density stress in juvenile rainbow trout (Oncorhynchus mykiss) through dietary nano-selenium: Effects on growth, antioxidant activity, and immune response - Mashooq Ali; Aqsa Akram; Farid Ahmad Jan; Aziz Ahmad; Ashiq Hussain; Fahim Ullah Khan; Muhammad Arshad (Journal of Trace Elements in Medicine and Biology, 2025)

The weight reducing effects of naltrexone-bupropion among obese psychiatric and non-psychiatric patients: a systematic review - Hafsah Alim Ur Rahman; Muhammad Ahmed Ali Fahim; Unaiza Naeem; Syed Hassan Ahmed; Muhammad Youshay Jawad; Hareem Arshad; Anil Kalyoncu; Mujeeb U. Shad; Ahmad Hameed (Psychopharmacology, 2025)

Pretreatment with probiotics (Bacillus safensis NMCC-189 and Bacillus clausii) prevents epileptogenesis in mice via modulation of BBB integrity, oxidative stress, and neurotransmitter balance - Maryam Khan Sherwani; Jehan Zeb Khan; Shakira Ghazanfar; Fahim Hilal; Rimsha Noor; Muhammad Khalid Tipu (Inflammopharmacology, 2025)

Selection criteria for the enhancement of nitrogen use efficiency in wheat using two step association analysis - Muhammad Amjad; Siddique Ahmad; Fahim Ullah Khan; Rafi Ullah; Iltaf Ullah; Muhammad Zahid Shah; Umar Bin Qasim (Vegetos, 2025)

Native plantations foster phylogenetic cohesion while nonnative plantations promote higher species turnover in understory vegetation in subtropical managed forest - Shoaib Ilyas; Sehrish Sadia; Mr Nadeem; Abeer Al-Andal; Asma Jabeen; Fahim Arshad; Sanaullah Sattar; Zarafshan Abbas; Muhammad Waheed (Journal of Environmental Management, 2025)

Functional trait variability and adaptive strategies of Genus Carex along the elevation gradients - Muhammad Waheed; Fahim Arshad; Muhammad Manzoor; Syed Waseem Gillani; Abeer Al-Andal; Kaniz Fatima (Flora, 2025)

Predicting ground-level PM 2.5 using high-resolution satellite imagery and machine learning algorithms with ground-based validation - Muhammad Hamza Tariq; Musawar Hussain; Muhammad Mahad Khaliq; Talha Saeed; Michael Howard Bergin; Muhammad Fahim Khokhar (International Journal of Remote Sensing, 2025)

Vanadium dioxide - Perovskite tandem smart windows achieve full-spectrum modulation via plasmonic Fabry-Pérot engineering - Qiuyi Shi; Bowen Li; Yuwei Du; Sai Liu; Rui Zhang; Cancheng Jiang; Xin Li; Muhammad Fahim; Irum Firdous; Johnny C.Y. Ho; Chi Yan Tso (Chemical Engineering Journal, 2025)

Trait plasticity and invasion success of Ageratum conyzoides in subtropical urban landscapes - Muhammad Waheed; Fahim Arshad; David M. Richardson; Abeer Al-Andal; Kaniz Fatima (Urban Ecosystems, 2025)

Taxonomic implications of pollen morphometric features for identification of arid and semi-arid arecaceae taxa - Hafiza Ayesha Rahim; Shabnum Shaheen; Muhammad Waheed; Nidaa Harun; Tahira Alyas; Fahim Arshad; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (Genetic Resources and Crop Evolution, 2025)

Utilizing genetic resources to develop yellow rust-resistant and high-yielding wheat genotypes across diverse environments - Hassan Mujtaba; Fahim Ullah Khan; Muhammad Sufyan; Israr Ud Din; Manzoor Ahmad; Asad Shah; Umair Bin Qasim (Genetic Resources and Crop Evolution, 2025)

Optimizing agroforestry systems through traditional ecological knowledge: a sustainable model for tree species selection in semi-arid lowland region - Muhammad Waheed; Fahim Arshad; Kaniz Fatima; Asma Jabeen; Abeer Al-Andal; Abdullayev Abdulla Fayzulla Ugli; Baxtigul Nurullayeva; Oygul Khujaniyozova (Agroforestry Systems, 2025)

Identification of the blue-sky conditions in Punjab, Pakistan by exploiting satellite and ground-based observations, and policy implications - Hira Saif; Talha Saeed; Musawar Hussain; Afnan Ullah; Muhammad Fahim Khokhar (International Journal of Remote Sensing, 2025)

Geo-spatial distribution of air pollutants in urban area and its potential health risk analysis solutions - Fajar Waheed; Nusrat Ehsan; Rabiya Nasir; Waqas Ahmed Khan; Muhammad Fahim Khokhar; Laila Shahzad; Aqil Tariq; Hira Afzal; Qamar uz Zaman (Urban Climate, 2025)

Genetic diversity in wheat landraces for agronomic traits and yellow rust resistance - Shamim Khan; Niaz Ali; Fahim Ullah Khan; Israr Ud Din; Muhammad Amjad; Israr Ahmad (Genetic Resources and Crop Evolution, 2025)

Food security and economic resilience of wild snake gourd (Trichosanthes cucumerina subsp. Cucumerina) under different host trees in subtropical managed forests - Muhammad Waheed; Fahim Arshad; Murad Muhammad; Abeer Hashem; Mohamad Alnafissa; Elsayed Fathi Abd-Allah; Valisher Sapayev (Agroforestry Systems, 2025)

Integrative taxonomy and multigene phylogeny uncover three novel taxa of the genus Clitopilus from southern Punjab, Pakistan - Muhammad Asif; Malka Saba; Wajahat Akram; Fazli Maula; Fahim Ullah; Momal Batool; Mohsin Ullah; Irmgard Krisai-Greilhuber; Mubashar Raza (Mycological Progress, 2025)

Sustainable high-performance density—nanoporous composite wood for water evaporation-induced electricity generation - Man Yi Wong; Abhishek Gautam; Kaixin Lin; Jianheng Chen; Tsz Chung Ho; Muhammad Fahim; Xu Chen; Aiqiang Pan; Chi Yan Tso (Chemical Engineering Journal, 2025)

Invasion by the non-native tree Vachellia farnesiana alters the understory composition of plants and soil properties in a managed forest in the subtropical region of Pakistan - Muhammad Waheed; Shiekh Marifatul Haq; Fahim Arshad; David M. Richardson (Plant Ecology, 2025)

Bacillus subtilis (NMCC-path-14) ameliorates acute phase of arthritis via modulating NF-κB and Nrf-2 signaling in mice model - Muhammad Usama Mazhar; Sadaf Naz; Tayyaba Zulfiqar; Jehan Zeb Khan; Fahim Hilal; Shakira Ghazanfar; Muhammad Khalid Tipu (Inflammopharmacology, 2025)

Adaptive floristic diversity and ecological responses to environmental gradients in the saline soil ecosystem - Sehrish Sadia; Muhammad Waheed; Fahim Arshad; Abeer Al-Andal; Mubashrah Munir; Asma Jabeen; Samreen Aslam (Journal for Nature Conservation, 2025)

Scenario-based HEC-RAS 2D unsteady flow analysis of Shisper Lake for GLOF risk assessment - Junaid Aziz Khan; Muhammad Qamar Javed Pirzada; Muhammad Fahim Khokhar (Natural Hazards, 2025)

Catalytic-assisted remediation and phytotoxicity evaluations of organic pollutants in the presence of metal-doped Bi2O3-based NPs catalyst - Farah Fahim; Muhammad Imran; Muhammad Ramzan; Zarish Nazeer; Awais Ali; Haﬁz M.N. Iqbal (Journal of Environmental Management, 2025)

Evaluating satellite-based precipitation products for spatiotemporal drought analysis - Hussain Masood Khan; Muhammad Fahim Aslam; Muhammad Waseem; Hafiz Kamran Jalil Abbasi; Ali Iftikhar; Faraz Ul Haq (Journal of Arid Environments, 2024)

In-depth analysis of ambient air pollution changes due to the COVID-19 pandemic in the Asian Monsoon region - Mohd Talib Latif; Noorain Purhanudin; Nur Zulaikha Mohd Afandi; Maria Obiminda L. Cambaliza; Nor Diana Abdul Halim; Nor Syamimi Sufiera Limi Hawari; To Thi Hien; Ohnmar May Tin Hlaing; Warnakulasuriya Roshani Loreta Hiranthi Jansz; Muhammad Fahim Khokhar; Puji Lestari; Shih-Chun Candice Lung; et al. (Science of The Total Environment, 2024)

Drivers of municipal water security and vulnerability in Pakistan: A case study of Mardan, Khyber Pakhtunkhwa - Kamran; Junaid Aziz Khan; Fasiha Safdar; Umer Khayyam; Iftikhar Hussain Adil; Abdul Waheed; Muhammad Fahim Khokhar (Groundwater for Sustainable Development, 2024)

Adaptive convergence and divergence underpin the diversity of Asteraceae in a semi-arid lowland region - Muhammad Waheed; Fahim Arshad (Flora, 2024)

Application of surface energy balance Algorithm for land (SEBAL) for mapping spatiotemporal evapotranspiration over various climatic zones of Pakistan - Benazeer Iqbal; Muhammad Ali; Beena Fahim; Jabir Nazir (Advances in Space Research, 2024)

Transcription factor ZmDof22 enhances drought tolerance by regulating stomatal movement and antioxidant enzymes activities in maize (Zea mays L.) - Liru Cao; Feiyu Ye; Abbas Muhammad Fahim; Chenchen Ma; Yunyun Pang; Xin Zhang; Qianjin Zhang; Xiaomin Lu (Theoretical and Applied Genetics, 2024)

Assessment of textile effluent treatment by immobilized Trametes pubescens MB 89 for plant growth promotion - Uroosa Ejaz; Saima Zakir; Zainul Abideen; Bushra Fahim; Waniya Shaikh; Faryal Shakil; Fizza Haroon Mirza; Syed Wasi Haider; Adnan Khan; Muhammad Sohail (Environmental Science and Pollution Research, 2024)

In-depth characterization of particulate matter in a highly polluted urban environment at the foothills of Himalaya–Karakorum Region - Bahadar Zeb; Khan Alam; Zhongwei Huang; Fatma Öztürk; Peng Wang; Lyudmila Mihaylova; Muhammad Fahim Khokhar; Said Munir (Environmental Science and Pollution Research, 2024)

Comprehensive Analysis of the DnaJ/HSP40 Gene Family in Maize (Zea mays L.) Reveals that ZmDnaJ96 Enhances Abiotic Stress Tolerance - Liru Cao; Guorui Wang; Abbas Muhammad Fahim; Yunyun Pang; Qianjin Zhang; Xin Zhang; Zhenghua Wang; Xiaomin Lu (Journal of Plant Growth Regulation, 2024)

Toxicological profile and potential health concerns through metals and trace elements exposure in brick kiln workers from Lahore, Pakistan - Talha Saeed; Naeem Akhtar Abbasi; Muhammad Talha Zahid; Noor Fatima; Kaleem Ullah; Muhammad Fahim Khokhar (Environmental Geochemistry and Health, 2024)

Remimazolam versus propofol for sedation in gastrointestinal endoscopy and colonoscopy within elderly patients: a meta-analysis of randomized controlled trials - Wania Ahmer; Sahar Imtiaz; Daniyal Muhammad Alam; Khadija Ahmed; Barka Sajid; Juvairia Yousuf; Sunny Asnani; Muhammad Ahmed Ali Fahim; Rahmeen Ali; Marium Mansoor; Muhammad Talha Safdar; Muhammad Umair Anjum; et al. (European Journal of Clinical Pharmacology, 2024)

Reduced toxic effects of nano‑copper sulfate in comparison of bulk CuSO4 on biochemical parameters in the Rohu (Labeo rohita) - Azka Anwar; Fahim Ullah Khan; Waqar Younas; Muhib Zaman; Muhammad Noorullah; Li'ang Li; Amina Zuberi; Youji Wang (Toxicology in Vitro, 2024)

Effects of acclimation temperature on growth, physiology and thermal tolerance of the juvenile grass carp Ctenopharyngodon idella - Fahim Ullah Khan; Waqar Younas; Yueyong Shang; Zhihan Tu; Muhammad Ismail Khan; Amina Zuberi; Youji Wang (Aquaculture, 2024)

Physiological and histopathological effects of polystyrene nanoparticles on the filter-feeding fish Hypophthalmichthys molitrix - Muhib Zaman; Fahim Ullah Khan; Waqar Younas; Muhammad Noorullah; Imdad Ullah; Li’ang Li; Amina Zuberi; Youji Wang (Science of The Total Environment, 2024)

Exploration of microplastic concentration in indoor and outdoor air samples: Morphological, polymeric, and elemental analysis - Khadija Sharaf Din; Muhammad Fahim Khokhar; Shahid Ikramullah Butt; Abdul Qadir; Farhan Younas (Science of The Total Environment, 2024)

Beyond the aging spine – a systematic review of functional changes in the human brain in cervical spondylotic myelopathy - Ali Fahim Khan; Fauziyya Muhammad; Esmaeil Mohammadi; Christen O’Neal; Grace Haynes; Sanaa Hameed; Brynden Walker; Michael L. Rohan; Andriy Yabluchanskiy; Zachary Adam Smith (GeroScience, 2023)

Assessing pyrolysis performance and product evolution of various medical wastes based on model-free and TG-FTIR-MS methods - Fahim Ullah; Guozhao Ji; Lei Zhang; Muhammad Irfan; Zegang Fu; Zakia Manzoor; Aimin Li (Chemical Engineering Journal, 2023)

Experimental behaviour of unreinforced and confined rat-trap bond masonry - Muhammad Haris; Mohammad Ashraf; Muhammad Fahim; Samiullah (European Journal of Environmental and Civil Engineering, 2023)

Aridity-driven changes in structural and physiological characteristics of Buffel grass (Cenchrus ciliaris L.) from different ecozones of Punjab Pakistan - Amina Ameer; Farooq Ahmad; Naila Asghar; Mansoor Hameed; Khawaja Shafique Ahmad; Ansar Mehmood; Fahim Nawaz; Muhammad Asif Shehzad; Sahar Mumtaz; Muhammad Kaleem; Ummar Iqbal (Physiology and Molecular Biology of Plants, 2023)

Microplastics pollution in agricultural farms soils: preliminary findings from tropical environment (Klang Valley, Malaysia) - Sarva Mangala Praveena; Muhammad Aiman Fahim Ishak Hisham; Ayu Lana Nafisyah (Environmental Monitoring and Assessment, 2023)

Antibiotics induced changes in nitrogen metabolism and antioxidative enzymes in mung bean (Vigna radiata) - Marium Fiaz; Iftikhar Ahmed; Sumara Masood Ul Hassan; Adnan Khan Niazi; Muhammad Fahim Khokhar; Zeshan; Muhammad Ansar Farooq; Muhammad Arshad (Science of The Total Environment, 2023)

Optimization of Citric Acid and EDTA Levels Under Ni Stress Using Rapeseed Brassica napus L. for Phytoremediation - Humera Nawaz; Naila Asghar; Aamir Ali; Amina Ameer; Muhammad Asif Shehzad; Fahim Nawaz; Ansar Mehmood; Muhammad Sajjad Iqbal; Ummar Iqbal; Muhammad Kaleem; Ameer Khan; Khawaja Shafique Ahmad (Water, Air, & Soil Pollution, 2023)

Biochar Amendment in Combination with Endophytic Bacteria Stimulates Photosynthetic Activity and Antioxidant Enzymes to Improve Soybean Yield Under Drought Stress - Fahim Nawaz; Rashid Rafeeq; Sadia Majeed; Muhammad Shoaib Ismail; Muhammad Ahsan; Khawaja Shafique Ahmad; Ahsan Akram; Ghulam Haider (Journal of Soil Science and Plant Nutrition, 2023)
The beneficial effects of biochar (BC) and plant growth-promoting bacteria (PGPR) to increase crop yields under harsh environments have been widely reported. However, the knowledge on the synergistic effects of BC and PGPR to induce drought tolerance in oilseeds is scant. In the present study, the effects of cotton sticks derived BC together with PGPR strains ( Paraburkholderia phytofirmans and Bacillus sp.) were examined in water-stressed soybean plants. Initially, the BC application rates (1% and 2%) for soybean were optimized in a pilot experiment (experiment I), and the most effective level (1%) was selected for further studies together with PGPR in the second experiment. The soybean plants were raised in pots under semi-controlled conditions and were subjected to drought stress (25–30% water holding capacity) at pod formation stage. In comparison with control, the drought-mediated decrease in photosynthetic pigments and gas exchange characteristics was markedly lower in BC and PGPR-treated plants. However, the maximum increase in photosynthetic (12–30%) and the enzymatic antioxidant activities (5–20%) was recorded in plants treated with BC + P. phytofirmans , whereas no further significant increase was observed in plants treated with combined BC and Bacillus sp. under water deficit conditions. Similarly, the combined BC and P. phytofirmans application considerably increased the grain yield (14%) under drought stress conditions. We conclude that the combined application of BC + P. phytofirmans could be utilized as an effective strategy to improve soybean yield in dry arid regions.

Role of financial development, foreign direct investment inflow, innovation in environmental degradation in Pakistan with dynamic ARDL simulation model - Ali Jan; Zhao Xin-gang; Samreen Fahim Babar; Muhammad Kamran Khan (Environmental Science and Pollution Research, 2023)

Improving drought mitigation strategies and disaster risk reduction through MODIS and TRMM-based data in relation to climate change over Pakistan - Shahzad Ali; Abdul Basit; Tyan Alice Makanda; Inamullah; Fahim Ullah Khan; Muhammad Sajid; Tamseela Riaz; Hira Farooq Abbasi; Manzoor; Amir Sohail (Environmental Science and Pollution Research, 2023)

High power-output and highly stretchable protein-based biomechanical energy harvester - Xiangkun Bo; Kindness A. Uyanga; Lingyun Wang; Irum Firdous; Jihong Shi; Weilu Li; Jasim M. Almardi; Muhammad Fahim; Fei Liu; Huanlin Lyu; Walid A. Daoud (Chemical Engineering Journal, 2023)

Correction to: Eco-friendly strategies for the management of Curvularia spicifera through phytobiocides and biological antagonists - Palwasha; Siraj ud Din; Muhammad Fahim (European Journal of Plant Pathology, 2023)

Observed and predicted precipitation variability across Pakistan with special focus on winter and pre-monsoon precipitation - Fasiha Safdar; Muhammad Fahim Khokhar; Fatimah Mahmood; Muhammad Zeeshan Ali Khan; Muhammad Arshad (Environmental Science and Pollution Research, 2023)

Effect of selenium accumulation on foraging behavior of pollinators and seed yield in Trifolium alexandrinum L. - Muhammad Awais Ahmad; Mudssar Ali; Shafqat Saeed; Fahim Nawaz (Environmental Science and Pollution Research, 2022)

Eco-friendly strategies for the management of Curvularia spicifera through phytobiocides and biological antagonists - Palwasha; Siraj ud Din; Muhammad Fahim (European Journal of Plant Pathology, 2022)

Remote sensing strategies to monitoring land use maps with AVHRR and MODIS data over the South Asia regions - Shahzad Ali; Huang An Qi; Malak Henchiri; Zhang Sha; Fahim Ullah Khan; Muhammad Sajid; Jiahua Zhang (Environmental Science and Pollution Research, 2022)

Coupling biochar with microbial inoculants improves maize growth and nutrients acquisition under phosphorous-limited soil - Hafiz Muhammad Rashad Javeed; Rimsha Naeem; Mazhar Ali; Rafi Qamar; Muhammad Aqeel Sarwar; Fahim Nawaz; Atique-ur-Rehman; Muhammad Shehzad; Amjad Farooq; Haseeb-ur-Rehman; Samina Khalid; Khuram Mubeen; et al. (Acta Physiologiae Plantarum, 2022)

Evaluation of agro-morphological traits, seed characterization and genetic diversity of local rice (Oryza sativa L.) varieties of Pakistan - Urooj Fazal; Israr Ud Din; Amir Muhammad Khan; Fahim Ullah Khan; Mudassar Nawaz Khan; Navid Iqbal; Muhammad Ibrahim; Sajid Ali Khan Bangash (Genetic Resources and Crop Evolution, 2022)

Impact assessment of drought monitoring events and vegetation dynamics based on multi-satellite remote sensing data over Pakistan - Shahzad Ali; Abdul Basit; Jian Ni; Manzoor; Fahim Ullah Khan; Muhammad Sajid; Muhammad Umair; Tyan Alice Makanda (Environmental Science and Pollution Research, 2022)

GhCDNC and GhCYP706B1 genes mediate gossypol biosynthesis in upland cotton - Hira Maryam; Zulfiqar Ali; Muhammad Abu Bakar Saddique; Fahim Nawaz (Molecular Biology Reports, 2022)

Genome wide analysis of DWARF27 genes in soybean and functional characterization of GmD27c reveals eminent role of strigolactones in rhizobia interaction and nodulation in Glycine max - Naveed ur Rehman; Farhat Abbas; Muhammad Imran; Intikhab Alam; Muhammad Imran; Ihteram Ullah; Muhammad Riaz; Fahim Ullah Khan (Molecular Biology Reports, 2022)

Pretreatment with Chitosan Arbitrates Physiological Processes and Antioxidant Defense System to Increase Drought Tolerance in Alfalfa (Medicago sativa L.) - Ghulam Mustafa; Muhammad Asif Shehzad; M. Hammad Nadeem Tahir; Fahim Nawaz; Gulzar Akhtar; Muhammad Asaad Bashir; Abdul Ghaffar (Journal of Soil Science and Plant Nutrition, 2022)

The genetic drivers for the successful invasive potential of a generalist bird, the House crow - Farheena Iqbal; Urszula Krzeminska-Ahmadzai; Qasim Ayub; Robyn Wilson; Beng Kah Song; Muhammad Fahim; Sadequr Rahman (Biological Invasions, 2022)

First report of Neopestalotiopsis clavispora causing postharvest fruit rot of loquat in Pakistan - Muhammad Fahim Abbas; Sana Batool; Tamoor Khan; Muhammad Rashid (Journal of Plant Pathology, 2022)

Comparative seismic performance assessment of RC and RC/ECC hybrid frame structures: a shake table study - Fasih Ahmed Khan; Muhammad Rashid; Sajjad Wali Khan; Muhammad Rizwan; Yasir Irfan Badrashi; Muhammad Fahim; Muhammad Ashraf Tanoli; Wasim Khaliq; Akhtar Gul (Innovative Infrastructure Solutions, 2022)

Biochar and slow-releasing nitrogen fertilizers improved growth, nitrogen use, yield, and fiber quality of cotton under arid climatic conditions - Sobia Manzoor; Muhammad Habib-ur-Rahman; Ghulam Haider; Iqra Ghafoor; Saeed Ahmad; Muhammad Afzal; Fahim Nawaz; Rashid Iqbal; Mubashra Yasin; Tanveer-ul-Haq; Subhan Danish; Abdul Ghaffar (Environmental Science and Pollution Research, 2022)
The efficiency of nitrogenous fertilizers in South Asia is on a declining trajectory due to increased losses. Biochar (BC) and slow-releasing nitrogen fertilizers (SRNF) have been found to improve nitrogen use efficiency (NUE) in certain cases. However, field-scale studies to explore the potential of BC and SRNF in south Asian arid climate are lacking. Here we conducted a field experiment in the arid environment to demonstrate the response of BC and SRNF on cotton growth and yield quality. The treatments were comprised of two factors, (A) nitrogen sources, (i) simple urea, (ii)neem-coated urea, (iii)sulfur-coated urea, (iv) bacterial coated urea, and cotton stalks biochar impregnated with simple urea, and (B) nitrogen application rates, N 1 =160 kg ha -1 , N 2 = 120 kg ha -1 , and N 3 = 80 kg ha -1 . Different SRNF differentially affected cotton growth, morphological and physiological attributes, and seed cotton yield (SCY). The bacterial coated urea at the highest rate of N application (160 kg ha -1 ) resulted in a higher net leaf photosynthetic rate (32.8 μmol m -2 s -1 ), leaf transpiration rate (8.10 mmol s -1 ), and stomatal conductance (0.502 mol m -2 s -1 ), while leaf area index (LAI), crop growth rate (CGR), and seed cotton yield (4513 kg ha -1 ) were increased by bacterial coated urea at 120 kg ha -1 than simple urea. However, low rate N application (80 kg ha -1 ) of bacterial coated urea showed higher nitrogen use efficiency (39.6 kg SCY kg -1 N). The fiber quality (fiber length, fiber strength, ginning outturn, fiber index, and seed index) was also increased with the high N application rates than N2 and N3 application. To summarize, the bacterial coated urea with recommended N (160 kg ha -1 ) and 75% of recommended N application (120 kg ha -1 ) may be recommended for farmers in the arid climatic conditions of Punjab to enhance the seed cotton yield, thereby reducing nitrogen losses.

Role of financial development, environmental-related technologies, research and development, energy intensity, natural resource depletion, and temperature in sustainable environment in Canada - Muhammad Kamran Khan; Samreen Fahim Babar; Bahareh Oryani; Vishal Dagar; Abdul Rehman; Abdulrasheed Zakari; Muhammad Owais Khan (Environmental Science and Pollution Research, 2022)

Comparative Effects of Individual and Consortia Plant Growth Promoting Bacteria on Physiological and Enzymatic Mechanisms to Confer Drought Tolerance in Maize (Zea mays L.) - Muhammad Saleem; Fahim Nawaz; Muhammad Baqir Hussain; Rao Muhammad Ikram (Journal of Soil Science and Plant Nutrition, 2021)
Mitigation strategies based on plant–microbe interactions to increase the performance of plants under water-deficit conditions are well documented. However, little is known about a suitable consortium of bacterial inoculants and underlying physiological and enzymatic events to improve drought tolerance in maize. We performed laboratory and pot experiments to understand the synergistic interactions among plant growth-promoting bacteria to alleviate the drought-induced damages in maize. Initially, ten bacterial strains were evaluated for their osmotic stress tolerance capacity by growing them in a media containing 0, 10, 20, and 30% polyethylene glycol (PEG-6000). Also, the seeds of a drought tolerant (NK-6654) and sensitive (SD-626) maize cultivar were inoculated with these bacterial strains in the first pot experiment to determine their effects on the growth and physiological processes. Later, in the second pot experiment, the best performing inoculants were selected to study the individual and synergistic effects of bacterial inoculation to confer drought tolerance in maize. Our findings showed that the inoculation with tolerant strains resulted in higher photosynthetic activity (25–39%), maintenance of leaf water status (14–18%) and pigments (27–32%), and stimulation of antioxidant machinery (28–38%) than no inoculation in water-stressed maize seedlings. Moreover, the treatment with bacteria consortia further stimulated the drought protective mechanisms and resulted in higher efficiency of photosynthetic (47–61%) and antioxidant systems (42–62%) than the individual inoculants under water-deficit conditions. We conclude that the inoculation with microbial consortia regulates water uptake, photosynthetic performance, and stress metabolites to minimize drought-induced damages in maize.

Correction to: Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

Screening of wheat (Triticum aestivum L.) genotypes for drought tolerance using polyethylene glycol - Muhammad Adnan Bukhari; Adnan Noor Shah; Shah Fahad; Javaid Iqbal; Fahim Nawaz; Abdul Manan; Mohammad Safdar Baloch (Arabian Journal of Geosciences, 2021)

Variability of Provincial Capital Rainfall in Pakistan Using Wavelet Transformation - Muhammad Fahim Akhter; Shaheen Abbas (Pure and Applied Geophysics, 2021)

Investigating the flood damages in Lower Indus Basin since 2000: Spatiotemporal analyses of the major flood events - Salman Atif; Muhammad Umar; Fahim Ullah (Natural Hazards, 2021)

Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafiz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

Sulfate-Based Fertilizers Regulate Nutrient Uptake, Photosynthetic Gas Exchange, and Enzymatic Antioxidants to Increase Sunflower Growth and Yield Under Drought Stress - Bilal Ahamid Shafiq; Fahim Nawaz; Sadia Majeed; Muhammad Aurangzaib; Abdullah Al Mamun; Muhammad Ahsan; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muqarrab Ali; Sarfraz Hashim; Tanveer ul Haq (Journal of Soil Science and Plant Nutrition, 2021)
The challenging impact of drought to agricultural productivity requires the adoption of mitigation strategies with a better understanding of underlying mechanisms responsible for drought tolerance. The present study aimed at investigating the effects of sulfur-based fertilizers on mitigation of drought stress in sunflower. Sulfate-containing fertilizers, viz., ammonium sulfate, zinc sulfate, magnesium sulfate, potassium sulfate, and gypsum, were initially evaluated at two different rates (10 and 20 mg kg −1 soil equivalent to 20 and 40 kg ha −1 , respectively) for nutrient uptake and growth-promoting traits in sunflower seedlings (cv. Hysun-33). The best performing fertilizer (gypsum) was then selected to evaluate the response of sunflower under drought stress imposed at flowering stage for three weeks (25–30% water holding capacity). Results indicated significant amelioration of drought stress with higher activity of photosynthetic apparatus, upregulation of antioxidative enzymes, and increased achene yield by gypsum application. In comparison to control, gypsum-treated plants (20 mg kg −1 soil) exhibited higher water status (32%), leaf photosynthetic rate (29%), transpiration rate (67%), and stomatal conductance (118%) under drought stress. The antioxidant enzyme activities of catalase, guaiacol peroxidase, and superoxide dismutase were also increased by 67%, 62%, and 126%, respectively, resulting in higher achene yield (19%) under water-deficit conditions. This study indicates that the application of sulfur-based fertilizers (gypsum) can be used to induce drought tolerance and obtain high sunflower yields under drought stress, and furthermore, it is a cost-effective strategy resulting in high benefit–cost ratio with respect to no gypsum application.

Salicylic Acid– and Ascorbic Acid–Induced Salt Tolerance in Mung bean (Vigna radiata (L.) Wilczek) Accompanied by Oxidative Defense Mechanisms - Maria Nawaz; Muhammad Yasin Ashraf; Ameer Khan; Fahim Nawaz (Journal of Soil Science and Plant Nutrition, 2021)

Physiological insights into sulfate and selenium interaction to improve drought tolerance in mung bean - Muhammad Aqib; Fahim Nawaz; Sadia Majeed; Abdul Ghaffar; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muhammad Naeem Tahir; Muhammad Aurangzaib; Hafiz Muhammad Rashad Javeed; Muhammad Habib-ur-Rahman; Muhammad Munir Usmani (Physiology and Molecular Biology of Plants, 2021)
The present study involved two pot experiments to investigate the response of mung bean to the individual or combined SO 4 2− and selenate application under drought stress. A marked increment in biomass and NPK accumulation was recorded in mung bean seedlings fertilized with various SO 4 2− sources, except for CuSO 4 . Compared to other SO 4 2− fertilizers, ZnSO 4 application resulted in the highest increase in growth attributes and shoot nutrient content. Further, the combined S and Se application (S + Se) significantly enhanced relative water content (16%), SPAD value (72%), photosynthetic rate (80%) and activities of catalase (79%), guaiacol peroxidase (53%) and superoxide dismutase (58%) in the leaves of water-stressed mung bean plants. Consequently, the grain yield of mung bean was markedly increased by 105% under water stress conditions. Furthermore, S + Se application considerably increased the concentrations of P (47%), K (75%), S (80%), Zn (160%), and Fe (15%) in mung bean seeds under drought stress conditions. These findings indicate that S + Se application potentially increases the nutritional quality of grain legumes by stimulating photosynthetic apparatus and antioxidative machinery under water deficit conditions. Our results could provide the basis for further experiments on cross-talk between S and Se regulatory pathways to improve the nutritional quality of food crops.

Monitoring of heavy metal pollution in urban and rural environments across Pakistan using House crows (Corvus splendens) as bioindicator - Farheena Iqbal; Qasim Ayub; Robyn Wilson; Beng Kah Song; Amin Talei; Keng Yoon Yeong; Andreas Aditya Hermawan; Muhammad Fahim; Sadequr Rahman (Environmental Monitoring and Assessment, 2021)

Evolutionary QTL-allele changes in main stem node number among geographic and seasonal subpopulations of Chinese cultivated soybeans - Abbas Muhammad Fahim; Fangdong Liu; Jianbo He; Wubing Wang; Guangnan Xing; Junyi Gai (Molecular Genetics and Genomics, 2021)

Investigating the tipping point of crop productivity induced by changing climatic variables - Fatimah Mahmood; Muhammad Fahim Khokhar; Zafar Mahmood (Environmental Science and Pollution Research, 2021)

Genetic manipulation of pea (Pisum sativum L.) with Arabidopsisˈs heat shock factor HsfA1d improves ROS scavenging system to confront thermal stress - Zamarud Shah; Arshad Iqbal; Fahim Ullah Khan; Hidayat Ullah Khan; Faran Durrani; Muhammad Zulfiqar Ahmad (Genetic Resources and Crop Evolution, 2020)

First report of post-harvest Fusarium rot caused by Fusarium oxysporum on Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Fahim Abbas; Aqleem Abbas; Rana Binyamin (Journal of Plant Pathology, 2020)

Morpho-molecular identification of Alternaria alternata causing leaf spot on loquat in Pakistan - Muhammad Fahim Abbas; Farah Naz; Sana Batool; Misbah Iqbal Qamar; Anam Moosa (Journal of Plant Pathology, 2020)

Correction to: Appraisal of disease-modifying potential of amlodipine as an anti-arthritic agent: new indication for an old drug - Sumera Qasim; Alamgeer; Saima Kalsoom; Muhammad Shahzad; Hafiz Muhammad Irfan; Muhammad Shoaib Zafar; Ishfaq Ali Bukhari; Fahim Vohra; Sibtain Afzal (Inflammopharmacology, 2020)

Appraisal of disease-modifying potential of amlodipine as an anti-arthritic agent: new indication for an old drug - Sumera Qasim; Alamgeer; Saima Kalsoom; Muhammad Shahzad; Hafiz Muhammad Irfan; Muhammad Shoaib Zafar; Ishfaq Ali Bukhari; Fahim Vohra; Sibtain Afzal (Inflammopharmacology, 2020)

Synergistic Long-Term Temperate Climate Nitrogen Removal Performance in Open Raceway Pond and Horizontal Subsurface Flow Constructed Wetland Operated Under Different Regimes - Raana Fahim; Xiwu Lu; Ghulam Ahmad Jilani; Hasan Mahdi; Muhammad Aslam (Water, Air, & Soil Pollution, 2020)

First report of Alternaria brown spot of Citrus reticulata cv. ‘Kinnow’ caused by Alternaria arborescens in Pakistan - Anam Moosa; Ayaz Farzand; Muhammad Fahim Abbas; Shahbaz Talib Sahi; Sajid Aleem Khan; Mark Lawrence Gleason (Journal of Plant Pathology, 2020)

Adaptations in Imperata cylindrica (L.) Raeusch. and Cenchrus ciliaris L. for altitude tolerance - Khawaja Shafique Ahmad; Ambreen Wazarat; Ansar Mehmood; Muhammad Sajid Aqeel Ahmad; Majid Mahmood Tahir; Fahim Nawaz; Haroon Ahmed; Mohsin Zafar; Aneela Ulfat (Biologia, 2020)

Effect of exogenous nitric oxide on sulfur and nitrate assimilation pathway enzymes in maize (Zea mays L.) under drought stress - Sadia Majeed; Fahim Nawaz; Muhammad Naeem; Muhammad Yasin Ashraf (Acta Physiologiae Plantarum, 2018)

Redox balance and DNA fragmentation in arsenic-exposed occupational workers from different industries of Pakistan - Maryam Raza; Ishrat Mahjabeen; Muhammad Fahim; Waqar Ahmad Malik; Asad Ullah Khan; Mahmood Akhtar Kayani; Ayesha Khan; Zertashia Akram (Environmental Science and Pollution Research, 2018)

First report of Diplodia seriata causing fruit rot of loquat in Pakistan - Muhammad Fahim Abbas; Farah Naz (Journal of Plant Pathology, 2018)

Effects of nickel toxicity on morphological and physiological aspects of osmoregulation in Typha domingensis (Typhaceae) populations - Noreen Akhtar; Mansoor Hameed; Abdul Hamid; Fahim Nawaz; Khawaja Shafique Ahmad; Jiabin Deng; Ansar Mehmood; Claudia Segovia-Salcedo; Muhammad Muslim Shahnaz; Abdul Qadir Khan (Limnology, 2018)

Correction to: Multi-sensor temporal assessment of tropospheric nitrogen dioxide column densities over Pakistan - Rabbia Murtaza; Muhammad Fahim Khokhar; Asma Noreen; Salman Atif; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2018)

Multi-sensor temporal assessment of tropospheric nitrogen dioxide column densities over Pakistan - Rabbia Murtaza; Muhammad Fahim Khokhar; Asma Noreen; Salman Atif; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2018)

Spatio-temporal assessment and seasonal variation of tropospheric ozone in Pakistan during the last decade - Asma Noreen; Muhammad Fahim Khokhar; Naila Zeb; Naila Yasmin; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2018)

Beating cold by being tough: impact of elevation on leaf characteristics in Phleum himalaicum Mez. endemic to Himalaya - Khawaja Shafique Ahmad; Mansoor Hameed; Abdul Hamid; Fahim Nawaz; Bushra Hafeez Kiani; Muhammad Sajid Aqeel Ahmad; Jiabin Deng; Farooq Ahmad; Imtiaz Hussain; Sana Fatima (Acta Physiologiae Plantarum, 2018)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Identification and future description of warming signatures over Pakistan with special emphasis on evolution of CO2 levels and temperature during the first decade of the twenty-first century - Khadija Haider; Muhammad Fahim Khokhar; Farrukh Chishtie; Waseem RazzaqKhan; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2017)

Investigating the nitrogen dioxide concentrations in the boundary layer by using multi-axis spectroscopic measurements and comparison with satellite observations - Muhammad Fahim Khokhar; Munazza Nisar; Asma Noreen; Waseem Razzaq Khan; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2017)

Foliar NK application mitigates drought effects in sunflower (Helianthus annuus L.) - Rai Altaf Hussain; Rashid Ahmad; Fahim Nawaz; Muhammad Yasin Ashraf; Ejaz Ahmad Waraich (Acta Physiologiae Plantarum, 2016)

Occurrence of potato mop-top virus in Northwest of Pakistan - Muhammad Arif; Murad Ali; Anayatur Rehman; Muhammad Fahim (European Journal of Plant Pathology, 2013)

Effectiveness of three potential sources of resistance in wheat against Wheat streak mosaic virus under field conditions - Muhammad Fahim; Philip J. Larkin; Steve Haber; Steve Shorter; Paul F. Lonergan; Garry M. Rosewarne (Australasian Plant Pathology, 2012)